Contribution of diabetes to amputations in sub-Sahara Africa: A systematic review and meta-analysis. Issue 3 (June 2022) - Boateng, Daniel; Ayellah, Bernard Bless; Adjei, David Nana; Agyemang, Charles
Highlights: Diabetes-related amputations remain a major global problem. Diabetes contributes substantially to the burden of amputations in sub-Sahara Africa. Infections and mortality are associated complications of diabetes-related amputations. Factors associated with diabetes-related amputations in SSA remain unclear. Abstract: Diabetes related amputations remain a major global problem, with devastating complications. We critically appraised relevant literature to quantify the prevalence of diabetes related amputations in sub-Saharan Africa (SSA). An electronic search was performed using the EMBASE and PubMed databases until 2020. Twenty-four out of 834 studies retrieved were included. The pooled prevalence of diabetic-related amputations was 36.9% (95%CI: 32.9%–40.8%). Complications of diabetes related amputations included infection, anaemia, foot deformity and mortality. The study revealed a substantial contribution of diabetes to the burden of amputations in SSA and suggests the need for further studies to assess how to reduce the incidence of diabetes, reduce the incidence of and or delay the progression of macro and microvascular complications of diabetes in SSA.